Generating audio-visual material for generic competences education - Palmer Rodríguez, Pere (2012)
Generic competences are a set of skills common to any degree course that students should acquire. Some examples of problems we can find in the teaching/learning process of these competences are: frequently lecturers do not know how to teach these transversal skills, the contents to teach are repeated in different courses and lecturers dedicate an important amount of time to explain them. Teamwork is included among these generic competences. This paper describes an experience designing audio-visual material which includes guidelines to help lecturers and students achieve successful teamwork. In the future, this idea could be transferred to other generic competences.